THE RISK ASSESSMENT OF THE RESIDUAL NEUROMUSCULAR BLOCKADE UNDER LAPAROSCOPIC OPERATIVE INTERVENTIONS - D. A. Kurenkov; E. M. Nikolaenko; S. Yu. Chizhevskaya; E. A. Evdokimov (Вестник анестезиологии и реаниматологии, 2017)
The risk degree of the residual curarization was identified for the tracheal extubation under laparoscopic intervention. It is shown by the quantitative neuromuscular monitoring and "total-blind" control under which recovery rate of the neuromuscular conduction and how soon on the operation completion the intensivists perform the tracheal extubation on a routine basis.